Utilization of Microsoft Office 365 at Jatiluhur 3 Elementary School - Dwi Purwanti (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The pandemic that hit the country of Indonesia brought changes in all sectors. Including the world of education. Face-to-face learning is forced to shift to distance learning. This is a challenge for educators and students. Especially for educators, creativity is required in distance learning. The pandemic that occurred in the 21st century demands that teachers be more professional, must not be blind to technology, and must be able to apply and adapt technology in learning. The fact is that not all teachers are technology literate. Therefore it is necessary to conduct training or increase in technology-based teaching competencies. The focus of this study is: 1) The concept and function of Microsoft office 365 in learning; (2) the use of Microsoft Forms and Sway in teaching at Jatiluhur 3 elementary school. The results of the study include: (1) Microsoft Office 365 has various features that are very supportive of learning; (2) The six teachers at Jatiluhur 3 elementary school have used Microsoft Office 365 with the Microsoft form and sway features.